(untitled) (inOpera Esercizi di lettura su testi contemporanei, 2024)
The contribution presents, in the first part, some reflections upon measure and intentions of the commentary on the poems of the first Milo De Angelis’ book, Somiglianze (1976), with some operational observations, and, in the second part, an interpretative exercise on a – in many ways – exemplary poem, Una generosità. The aim is to identify the constitutive elements of his note apparatus through a reasoned commentary, imagined in function of an annotated edition with a text general presentation (dating, location, overall structure, and main characteristics), followed by precise exegetical notes.